Device Compartment with Non-Woven Secondary Filter Medium for Diesel Engine Exhaust Vent - Dr. M Saravanan; Pradeep D N; Sindhoora R P; Vikneshver V; Chidambara Meena K (International Journal of Engineering and Management Research, 2023)
Transportation is a significant contributor to air pollution in many nations across the world, because of the large number of vehicles that are present on the roads. To reduce pollution from diesel engine vehicles, the Indian auto sector made its hard transition from BS4 to BS6 norms in April 2020. Selective Catalytic Reduction (SCR) and Diesel Particulate Filter (DPF) were included to the BSVI norms to evaluate the emission levels of the BS6 motor vehicle, but the BS4 norms do not include such an in-built filtration capability. However, it is mandatory to reduce the emission level in vehicles running on BS4 engine. This paper deals with the development of device compartment for filter fabric to be fitted as an attachment for various diesel engine vehicles and fabrication of non-woven filter fabric as a secondary medium. Through this additional fitting along the exhaust vent of BS4 diesel engine vehicles, soot particles can be arrested and reuse of BS4 engine is made possible.